Locked down or locked out? Trends in psychiatric emergency services utilization during the COVID-19 pandemic. Issue 2 (April 2023) - Duncan, Alison; Herrera, Carolina-Nicole; Okobi, Margaret; Nandi, Shurobhi; Oblath, Rachel
Objective: To estimate changes in Boston Emergency Services Team (BEST) psychiatric emergency services (PES) encounter volume (total and by care team) and inpatient disposition during the first 8 months of the COVID-19 pandemic. Methods: Data on 30, 657 PES encounters was extracted from the four-county, BEST reporting system. The study period consisted of the first 34 weeks of 2019 and 2020. This period corresponded to the first five stages of Massachusetts's COVID-19 public health restrictions: pre-lockdown, lockdown, Phase I, II and III reopenings. Descriptive and regression analyses were performed to estimate changes in encounter volume by care team and disposition. Results: Compared to the same period in 2019, covariate-adjusted, weekly PES encounters decreased by 39% (β = −0.40, 95% Confidence Interval (CI) = [−0.51, −0.28], p < 0.00) during the lockdown. PES volume remained significantly lower during Phase I reopening compared to the previous year but returned to 2019 levels during Phase II. The covariate-adjusted proportion of weekly encounters that led to inpatient admission significantly increased by 16% (CI = [0.11, 0.21], p < 0.00) for mobile crisis teams (MCTs) and significantly declined by 13% (CI = [−0.19, −0.07], p < 0.00) for BEST-designated emergency departments during the lockdown period compared to the prior year. Conclusions: The overall drop in PES utilization and the rise in inpatient admissions for MCT encounters suggests that during the early phases of the pandemic, patients delayed psychiatric care until they had a psychiatric crisis. Public health messaging about the lockdowns and absent equivalent messaging about the availability of telehealth services may have made patients more reluctant to seek psychiatric care.